'I am just a loser of higher education': a framework for comparative analysis of the value of adult higher education derived from a Chinese study. Issue 4 (3rd April 2022) - Guan, Shanshan; Abbas, Andrea
ABSTRACT: This paper proposes a unique framework for comparative analysis of different Adult Higher Education (AHE) systems. The framework combines, a conceptualisation of how students' outcomes are shaped by the way that they and their degree courses are positioned in stratified higher education systems with, insights about the effects of institutional practice and individual students' agency gained from applying Basil Bernstein's notion of pedagogic rights and underpinning concepts. The framework facilitates an exploration of structures and agencies manifesting through institutional practices, students' and graduates' experiences. The value of the framework is illustrated by an analysis of biographical interviews with twenty female, Chinese AHE students and ten graduates. It tracks an emergent process evident in students and graduates' descriptions of their disappointing emergent identities and limited employment progression. The framework provides a non-deterministic analysis that can inform how to comparatively analyse and improve AHE's contribution to societies and economies.